ECONOMIC MACRO INFLUENCE STUDY, CAPITAL, AND LIQUIDITY TO FINANCIAL PERFORMANCE AT LOCAL DEVELOPMENT BANK IN INDONESIA BEFORE AND AFTER AREA AUTONOMY - Moir Hasan; Khairul Anuar; Abdul Ghafar Ismail (Universitas Trisakti, 2009)
Purpose of this research is to know influence macro economic, capital, and liquidity to financial performance at local development bank (BPD) in Indonesia.This research is research explanatory, with research unit of all (population) Local Development Bank in Indonesia. Based on Indonesia Bank data there are 26 local development bank in Indonesia. Data collecting is done by using secondary data in the form of publication financial statements of local development bank of all Indonesia from the year 1996 until the year 2005 (during 10 years). Financial statements obtained from Indonesia bank head office and research bureau info bank. Research type applied is the causal relation by using census and secondary's data collecting and data analysis done through structural equation model (SEM). Result of this research indicates that : 1) macro variable of chartered investment counsel either before and also after area autonomy shows different result, before area autonomy doesn't have an effect on significant to financial performance, while after area autonomy influential significant; 2) variable capital influential significant to financial performance before area autonomy, while after area autonomy doesn't have an effect on significant; 3) variable liquidity before area autonomy influential significant to financial performance, and after area autonomy doesn't have an effect on significant.Keyword: macro economic, capital, liquidity, and financial performance.